METHOD OF HYDRAULIC CALCULATION OF TRANSFORMATION OF WATER RESERVOIR BOWLS UNDER THE INFLUENCE OF NATURAL AND ANTHROPOGENIC FACTORS (British Journal of Global Ecology and Sustainable Development, 2026)
Reservoirs are large hydraulic structures designed to perform functions such as managing water resources and their efficient use in economic sectors, as well as preventing or reducing the negative effects of catastrophic floods. Dams and weirs of reservoirs are designed to hold large masses of water, and during normal operation of reservoirs, processes such as the accumulation of water in the reservoir and its release during operation are observed, such as the accumulation of turbidity in the reservoir basin, erosion of banks and dams.Natural disasters (floods, high-water periods, etc.) and catastrophic situations associated with the operation of reservoirs have a significant negative impact on socio-economic infrastructure facilities, the population, and the ecosystem. At the same time, as a result of the breach of the reservoir dam (overflow), a large mass of water flows downstream through the overflow, a sharp increase in the flow velocity occurs, which leads to macro-meso-shaped deformation processes associated with the washing out of certain parts of the reservoir basin or its filling with muddy water, which leads to the formation of a relief of the riverbed with complex geometry. This situation, in turn, raises issues regarding the determination of the volume of water resources in the reservoir and their accounting. This article presents a hydraulic method for calculating the state of the relief of a reservoir basin that has undergone severe deformation.